Caracterização molecular de proetínas envolvidas nos mecanismos de homeostase de cobre em Xanthomonas citri subsp. citri - Freitas, Eliane Cristina de [UNESP] (2013)
Xanthomonas citri subsp. citri (Xac) is a plant pathogen that causes citrus canker. Genes encoding proteins related to tolerance to copper have been identified in the genome of Xac (copA and copB) and studies of molecular and biochemical characterization has been performed by our group. Copper-based compounds are used in the control of bacterial diseases in plants and the effectiveness of this process has been limited by the appearance of strains resistant to copper. Initially, Xac strains isolated in different States of the country were evaluated for growth in the presence of copper. The results showed that the strains isolated in the South have the higher tolerance to the metal. However, Southern blot analysis showed that some strains exhibited an identical profile in the genomic organization of ORFs involved in copper homeostasis when compared to the control strain (Xac, strain 306). The chromosomal genes copA and copB in Xac are organized in an operon whose transcription was previously shown to be induced and specific to copper. The ORF XAC3629, object of study in this work, is located upstream to copAB operon and encodes a protein homologous to CopL of X. axonopodis pv. vesicatoria. Gene expression analysis showed that the transcript of the ORF was also induced by copper and inactivation of the ORF by insertion of a transposon led to no expression of the operon copAB, suggesting that the ORF controls the expression of the operon. Furthermore, the XAC3629